Application of Advanced Emulsion Technology in the Food Industry: A Review and Critical Evaluation - Chen Tan; David Julian McClements (Foods, 2021)
The food industry is one of the major users of emulsion technology, as many food products exist in an emulsified form, including many dressings, sauces, spreads, dips, creams, and beverages. Recently, there has been an interest in improving the healthiness, sustainability, and safety of foods in an attempt to address some of the negative effects associated with the modern food supply, such as rising chronic diseases, environmental damage, and food safety concerns. Advanced emulsion technologies can be used to address many of these concerns. In this review article, recent studies on the development and utilization of these advanced technologies are critically assessed, including nanoemulsions, high internal phase emulsions (HIPEs), Pickering emulsions, multilayer emulsions, solid lipid nanoparticles (SLNs), multiple emulsions, and emulgels. A brief description of each type of emulsion is given, then their formation and properties are described, and finally their potential applications in the food industry are presented. Special emphasis is given to the utilization of these advanced technologies for the delivery of bioactive compounds.